"I think that is a better way to teach but …": EFL teachers' conflicting beliefs about grammar teaching. (August 2019) - Sato, Masatoshi; Oyanedel, Juan Carlos
Abstract: This study investigated teachers' beliefs regarding grammar instruction integrated into communicative teaching in an English-as-a-foreign-language (EFL) context, with a focus on conflicting beliefs. First, a survey was designed and implemented to examine teachers' beliefs about (a) L2 learning theories, (b) grammar instruction and communicative teaching, and (c) obstacles in implementing communicative teaching. In total, 498 school-level teachers completed the survey. Subsequently, nine teachers participated in focus-group interviews. The survey revealed overall support for teaching grammar via communicative methods. However, in the interview data, three types of conflicting beliefs were identified. First, theoretical conflicts pertained to the role that grammatical knowledge plays in developing communicative skills. Second, experiential conflicts were based on the teachers' unsuccessful experiences in using pair and group activities that resulted in a lack of student engagement. Third, contextual conflicts entailed beliefs about the compatibility of communicative teaching with the local socio-educational context. Teaching experiences positively and negatively mediated the conflicting beliefs. Overall, teachers' beliefs about how a L2 should be learned entailed a different set of beliefs from those about how a L2 can be taught.